Evaluation of reading performances in patients with primary glaucoma - Sidhu, Jasvinjeet Kaur (2023)
INTRODUCTION Glaucoma is the leading cause of irreversible blindness worldwide with primary open angle glaucoma (POAG) as the predominant subtype followed by primary angle closure glaucoma (PACG). Patients with advancing glaucoma suffer from increasing difficulty with daily living activities that require peripheral vision like reading. While there are effective medical interventions to minimize the progression of peripheral visual field loss in glaucoma, the acquired field loss is irreversible. OBJECTIVE To evaluate the reading performances in patients with primary glaucoma according to severity of visual field defect using daily reading materials. METHODOLOGY A cross sectional study was conducted involving patients with primary glaucoma between August 2020 and August 2022 at Glaucoma Clinic, Hospital Universiti Sains Malaysia (HUSM). The inclusion criteria include those with good central vision of ≥ 6/12. Baseline visual acuity, Humphrey visual field (HVF) monocular, binocular Esterman analysis and contrast sensitivity test was conducted. Severity of glaucoma was assessed using modified Hodapp-Anderson-Parish criteria, on the HVF of the better eye. Patients were asked to read five different reading materials, newspaper heading (0.9º), newspaper sub-heading (0.43º), newspaper print size (0.28º), pharmacy label print (0.28º) and bills (0.14º). All reading materials were in Bahasa Malaysia. The reading materials were presented on a pedestal at a reading distance of 40 cm from the subject, under a fixed light intensity of 500-600 lux. Reading performances were assessed by the number of words read and mistakes made within a minute of reading each material. A stopwatch was used to time the reading. RESULTS A total of 132 (42 mild, 45 moderate and 45 severe) patients with primary glaucoma were recruited. The mean reading speed decrease significantly with advancing glaucoma for all reading materials (p< 0.001). The difference in reading speed for newspaper print size, pharmacy label print and bill were statistically significant among all three groups of severity (p<0.001). Similarly, patients with severe glaucoma documented more mistakes in all five reading materials when compared to those with mild and moderate glaucoma. Patients documented more mistakes when reading smaller prints such as the newspaper print size, pharmacy label print and bill. After controlling confounding factors such as age, systemic comorbidities, education level, and occupation the outcomes were still significant.